Reposition and Role of Non-Governmental Organizations in North Sumatera Post-New Order: A Study of KSPPM, BITRA Indonesia, And PESADA - Dimpos Manalu; Johnson Pasaribu; Artha Lumbantobing; Vera A Pasaribu; Susi Yanti Halawa (Jurnal Mamangan, 2025)
This study aims to uncover the role and repositioning of non-governmental organizations (NGOs) in North Sumatra in the post-New Order era. Specifically, this study aims to uncover how NGOs reposition themselves towards the state/government, the market, and civil society—three major entities widely recognized in Public Administration studies. This is crucial considering that NGOs—as one of the important democratic actors in community empowerment and democratization in Indonesia—are situated within a constantly changing national socio-political landscape, as well as a global context that increasingly emphasizes the importance of multi-stakeholder collaboration. This study—taking into account the issues and areas discussed—focuses on three institutions: KSPPM, BITRA Indonesia, and PESADA. Using a qualitative-descriptive method, this study concludes several things: first, during the Reformation era, NGOs have repositioned themselves, no longer as opposition to the government, but as "critical partners"; second, despite the increasingly open political system, NGOs have not succeeded in building effective political relationships; third, along with the collapse of the New Order as their "common enemy," NGOs tend to experience fragmentation and sectarianism in the Reformation era; Fourth, in the Reformation era, NGOs in North Sumatra began to open up spaces for dialogue, negotiation, and technology, and actively encouraged the communities they supported to enter public spaces and positions; Fifth, NGOs in North Sumatra did not abandon "traditional" issues, but now tended to expand their issues and areas of concern; Sixth, the three institutions (KSPPM, BITRA, and PESADA) demonstrated greater program and financial capacity, although they still depended on funding institutions; Seventh, NGOs in North Sumatra tended to remain skeptical, even closed, in collaborating with private companies; Eighth, in the Reformation era, NGOs in North Sumatra increasingly took a side on gender issues, although in this regard there was—and were influenced by—active encouragement from their donors; which is no less important. The novelty of this research found a number of achievements that have been made by the three institutions, which make them worthy of public appreciation and trust to date.